AN EMPIRICAL ANALYSIS OF THE IMPACT OF TAX PLANNING ON CORPORATE TAX LIABILITY - Linatul Uyun (CV. Fahr Publishing, 2024)
This study aims to empirically examine the effect of tax planning on corporate tax liability among non-financial firms listed on the Indonesia Stock Exchange (IDX) during the period 2020–2022. Motivated by Indonesia’s post-pandemic fiscal reforms, particularly the implementation of the Harmonized Tax Law (UU HPP), this research addresses the gap in empirical literature on how tax planning operates in emerging markets with evolving regulatory structures. The study employs a quantitative explanatory approach using panel data regression (fixed-effects model) on 240 firm-year observations. Tax planning is proxied by Book-Tax Differences (BTD), while corporate tax liability is measured through the Effective Tax Rate (ETR). The findings reveal a significant negative relationship between BTD and ETR, indicating that firms engaging in higher levels of tax planning are able to reduce their reported tax liabilities. Control variables such as profitability (ROA) also show a significant influence, whereas firm size and leverage do not. The novelty of this study lies in its integration of recent fiscal policy shifts, firm-level financial indicators, and governance perspectives within the Indonesian context—an approach not widely explored in previous literature. Additionally, by focusing on a post-reform period marked by economic volatility, this study contributes contemporary evidence to the discourse on responsible and strategic tax behavior. In conclusion, tax planning proves to be an effective yet context-dependent tool for managing corporate tax burdens, with broader implications for regulatory design and corporate governance in emerging economies.